A prolonged divorce between economists and politicians - Napoleon Pop; Valeriu Ioan-Franc (Romanian Academy, National Institute for Economic Research, 2022)
The academic world says that the divorce between economists and politicians became visible during the financial crisis that began in 2008, when the economists were criticised for failing to preview the crisis, on the one hand, and, on the other hand, for the slowness in accompanying the solutions to remedy the crisis which should have been suggested by the politicians in an emergency situation, of financial collapse. The divorce itself has been lasting for a long time with the relationship deteriorating for many other reasons. In the background there is (1) an elite of Nobel prize winning economists with permanent training and inclination towards research and results worthy of consideration, and (2) a political class in a quasi-constant professional decline. It is a worrying fact, also publicly acknowledged. The 21st century, which marks the greatest technological advance of the fourth industrial revolution, started with avatars coming seemingly from nowhere. Yet, this century which began with so much hope, brings us in the face of yet another break between science and practice. The phenomenon we refer to in the current study is just a small part of what it should have been the collaboration between politicians and science in general, but the specifics of the divorce we approach in this essay is the fact that it deepens.
Keywords: A1; A11; B20; B52; H5; J18; 330; general economics; information and uncertainty; economic policies; politics and sociological system; national government policies; public policy